(untitled) (Journal of the College of Languages (JCL), 2024)
Abstract: Persian literature, after the spread of Islam in Pars, received a lot of influence from the subtle and rhetorical details of the Holy Quran. This effect is more in poetry than in prose because the weights of Persian poetry are closer to the melody of the Qur’an and its weights.The effectiveness of most of the prose works is only in the Quranic themes and words. Persian poetry that has benefited from various sciences of rhetoric, including semantics, eloquence and rhetoric. The degree and manner of influence of each of the didactic, lyrical, epic and travelogue literary types is different from the rhetorical points of the Quran. The instructions under educational literature have benefited the least from Quranic rhetoric. The maxim under educational literature have benefited the least from Quranic rhetoric. The travelogues share this as well as the admonitions, but in Ghanaian prose, we see the greatest use of Qur’anic rhetorical points by poets and writers.The travelogues share this as well as the maxim, but in lyrical prose we see the most use of Quranic rhetorical points by poets and writers. Hafez and Saadi have been more successful than others in this regard. Shahnameh is the best book of classical sustainability literature. Ferdowsi paid more attention to the translation of verses and words due to his sense of patriotism and adherence to the national language. But Ahmad Azizi borrows words and interpretations from the Qur’an with high frequency in his poems in contrast to Ferdowsi in contemporary sustainability literature. چکیده : ادبیات فارسی در پی گسترش دین اسلام در پارس از لطایف و دقایق بلاغی قرآن کریم تأثیر بسیاری پذیرفت . این تأثیر در نظم بیش از نثر است زیرا اوزان شعر فارسی به آهنگ کلام قرآن و وزنهای آن نزدیکی بیشتری دارد . از این‌ رو اثر پذیری اکثر آثار منثور صرفاً در مضامین و واژگان قرآنی است برخلاف شعر فارسی که از علوم مختلف بلاغت اعم از معانی، بیان و بدیع بهره گرفته است . میزان ونحوه ی تأثیر پذیری هر کدام از انواع ادبی تعلیمی ، غنائی ، پایداری و سفرنامه از نکات بلاغی قرآن متفاوت است . اندرزنامه ها تحت ادبیات تعلیمی کمترین بهره را از بلاغت قرآنی برده‌ اند . سفرنامه ها نیز مانند اندرزنامه ها در این امر اشتراک دارند اما در نثر غنائی شاهد بیشترین استفاده شعرا و نویسندگان از نکات بلاغی قرآنی هستیم . حافظ وسعدی نسبت به سایرین در این امر موفقتر بوده ‌اند . فردوسی در شاهنامه برترین کتاب ادبیات پایداری کلاسیک به دلیل داشتن حس وطن ‌دوستی و پایبندی به زبان ملی؛ بیشتر به ترجمه آیات و واژگان توجه داشته است اما احمد عزیزی در ادبیات پایداری معاصر برخلاف فردوسی از واژگان وتعبیرات قرآنی با بسامد بالا در اشعارش وام‌ گیری میکند . Received on 25/6/2023 Accepted on 20/8/2023 Published on 2/1/2024